Electroencephalography Findings in Autoimmune and Neuroinflammation-Related Epilepsies - Kim, Jeong-A; Albert, Dara V.F.; Weber, Amanda R.B. (Journal of Pediatric Epilepsy, 2018)
Autoimmune epilepsy occurs in association with localized central nervous system or systemic immune-mediated inflammation. Traditional anticonvulsant medications are frequently ineffective, and alternative approaches including immunomodulatory agents may be required. Identification of patients with autoimmune epilepsy may be challenging due to the variability of presentation and normal or nonspecific diagnostic results. Electroencephalography (EEG) features tend to include patterns of encephalopathy, generalized or focal interictal epileptiform abnormalities, or status epilepticus. Occasionally, specific EEG features may lend insight into the diagnosis. In this review article, we discuss EEG features of several suspected or proven immune-mediated pediatric epilepsies, including Rasmussen's encephalitis, idiopathic hemiconvulsion-hemiplegia syndrome, febrile infection-related epilepsy syndrome, epilepsies associated with autoantibodies to neuronal surface or intracellular antigens, and other systemic autoimmune diseases.
Keywords: electroencephalography; autoimmune epilepsy; pediatrics